Nitrogen dynamics and fertilisation use efficiency: carry‐over effect of crop limitation. (2nd December 2021) - Verdenal, T.; Spangenberg, J.E.; Dienes‐Nagy, Á.; Zufferey, V.; Spring, J.‐L.; Viret, O.; van Leeuwen, C.
Abstract: Background and Aims: Knowing the impact of cultural practices on nitrogen (N) dynamics in perennial crops is critical to promote N use efficiency. This study focused on the impact of crop regulation on the plant N dynamics, on the fruit N composition, and on the N fertilisation use efficiency. Methods and Results: A large crop load gradient was set in a homogeneous plot of the grape cultivar Chasselas. Fertilisation in the form of 15 N‐labelled foliar urea allowed the measurement of N uptake and partitioning among plant fractions. Dry mass, carbon, and N dynamics were assessed over two consecutive seasons. Crop regulation did not affect grape N concentration at harvest. Both N uptake and root N mobilisation were reduced in response to crop regulation. Fertilisation efficiency was higher under high‐yield conditions in terms of N uptake and grape N accumulation. The carry‐over effects of crop regulation in the following year were highlighted. Conclusions: Crop regulation strongly affects the overall plant N cycle, that is, uptake, distribution and release. Crop regulation improves must sugar concentration at harvest, while N concentration remained unchanged. The efficiency of N fertilisation varies greatly with crop load, which limits the interest of fertilisation under low‐yield conditions. Significance of the Study: These results contribute to the development of accurate nutrition models and sustainable cultural practices.